16m-9n-9m+12n-12=

Simple and best practice solution for 16m-9n-9m+12n-12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16m-9n-9m+12n-12= equation:


Simplifying
16m + -9n + -9m + 12n + -12 = 0

Reorder the terms:
-12 + 16m + -9m + -9n + 12n = 0

Combine like terms: 16m + -9m = 7m
-12 + 7m + -9n + 12n = 0

Combine like terms: -9n + 12n = 3n
-12 + 7m + 3n = 0

Solving
-12 + 7m + 3n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 7m + 12 + 3n = 0 + 12

Reorder the terms:
-12 + 12 + 7m + 3n = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 7m + 3n = 0 + 12
7m + 3n = 0 + 12

Combine like terms: 0 + 12 = 12
7m + 3n = 12

Add '-3n' to each side of the equation.
7m + 3n + -3n = 12 + -3n

Combine like terms: 3n + -3n = 0
7m + 0 = 12 + -3n
7m = 12 + -3n

Divide each side by '7'.
m = 1.714285714 + -0.4285714286n

Simplifying
m = 1.714285714 + -0.4285714286n

See similar equations:

| 12x+7=23+4x | | 9x-4=20+3x | | (x-.5)(x+.8)=0 | | 4x-12=x+18 | | (3x+7)(5x-7)=0 | | x^2=x^4 | | x^2-96x-636=0 | | 3x-12=x+18 | | M+n-2+2m-5n= | | 4x+3=-7(x+9) | | 1-x=5x+1 | | 6x-89=3x-8 | | -18-10x=73-31x | | 113-5x=4x+5 | | 1-x=5x-1 | | X^2+6x+4=5 | | sin(a)+sin(b)=1 | | (x-8)(x-1)=0 | | 71-4x=14x+21 | | 2x+12=-15x-7 | | =16x^3-20x^2-4x+15 | | 2(p+1)=16 | | 2x+-9=33 | | 2x*2x-6x+8=0 | | 5x-3=3+10 | | 12a*(-6bc)-4a= | | 1x-70=6 | | 1x-70=2 | | 20(x-6)=15x | | -3x-2(-x-5)+10= | | (x^2)-6x=7 | | 14-4(2x+3y)= |

Equations solver categories